The writing of where : graffiti and the production of writing spaces - Lesh, Charles N. (Writing, culture, and community practices series., 2022)
"The Writing of Where examines how graffiti writers in Boston write and rewrite various spaces within and across the city. Drawing on a four-year study with graffiti writers, this book explores how writing communities-particularly those marginalized by local processes of neoliberal space-produce public texts that at once challenge existing discourses of place and produce new, emergent writing spaces organized around alternative social principles"--